การคุ้มครองสิทธิในการดำเนินคดีของผู้ป่วยทางจิต: กรณีศึกษาด้านนิติจิตเวชศาสตร์ - ควรเดชะคุปต์ ธัชชัย (KASEM BUNDIT JOURNAL, 2021)
PURPOSES: To study the legal procedure and the rights of mental illness patients to be protected sufficiently during litigation. METHODS: Documentary research and analysis of psychiatric mental illness and the provision of laws related to forensic psychiatry. RESULTS: There was no clear procedure or provision during litigation for mental illness patients for sufficient human right protection. Insufficient understanding of various kinds of medical mental illness from legal point of view that could adversely affect rights protection for mental illness patients. CONCLUSIONS: The legal procedure for mental illness is recommended to be prioritized on rights protection and cure rather than legal punishment.